Effect of Yoganidra on Anxiety and Depressive Symptoms in Working Women - Kaur, Rupinder; Sharma, Sunil (International Research Journal of Ayurveda & Yoga, 2021)
In today’s scenario, Working women being housewife have to face many problems that are associated with several psychological symptoms. Anxiety and depressive symptoms might be a severe enough to cause significant other issues. Yoganidra is an effective technique and successful therapy to calm down and achieve a total transformation and overcome any kind of psychological disturbances. The purpose of the present study is to find out the effect of Yoganidra on the Level of Anxiety and depression in working women. A total of 120 working women were recruited from Patiala within the age range of 18-45 years. The result of the study revealed that in the Yoga Practitioners group of working women, a significant inverse level of Anxiety as compared to non-Yoga Practitioners groups of working women as well the depressive symptoms also depicts a significant inverse difference was found in Yoga practitioners group of working women as compared to the non-yoga practitioners group of working women.